Three Phase Bone Scintigraphy and Radiologic Evaluation in Poliostotic Fibrous Dysplasia: A Case Report (Annals of Medical Research, 2021)
None
Keywords: s : Poliostotic fibrous dysplasia, bone scintigraphy, Tc-99m MDP.